PERMASALAHAN YANG DISAMPAIKAN SISWA KEPADA GURU BK/KONSELOR - Aulia Khofifah; Afrizal Sano; Yarmis Syukur (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2017)
Problem is a situation that does not like it is, something you want removed, and something that can hinder or result in losses. The problems revealed in this study wanted the students to the issues presented BK teacher/counselor. This study aimed to describe the problems presented to the student teacher BK /counselors in high schools in the city of Padang can be seen from personal problems, learning problems, social problems, and career problems and the factors that encourage students and the results obtained. This type of research considered in a descriptive study using the questionnaire research instruments. 2430 samples of a total of 147 students study subjects that matter to teachers convey BK/counselor. Both students who come alone, students who were called and students recommendation.